ACHIEVEMENTS OF TASHKENT STATE LAW UNIVERSITY - Kudratillayev Jakhongir (European Science Publishing, 2025)
This article highlights the significant achievements of Tashkent State University of Law (TSUL) in 2023-2024. The article provides a detailed account of the university's success in securing international grants, its positions in prestigious rankings such as Times Higher Education, WURI, and RUR, students' accomplishments in international competitions, as well as achievements in academic activities and international cooperation. The conclusion draws insights into the university's development prospects, emphasizing TSUL's strengthening position in the global academic community and its leading role in Uzbekistan's higher education system.
Keywords: Tashkent State University of Law, international grants, Times Higher Education, Young University Rankings, THE Impact Ranking, WURI ranking, RUR ranking, academic exchange, international cooperation, sustainable development goals, innovative education.